Physical-intellectual badminton teaching intervention for children with intellectual disabilities - Wang, Yu; Zhou, Delai; Liu, Chuang; Long, Lingyu; Cheng, Gong (Frontiers in Psychology, 2025)
ObjectiveTo promote the healthy development of adolescents with intellectual disabilities, this study uses badminton to combine sports intervention with cognitive intervention to explore the content of sports teaching and cognitive intervention programs suitable for the learning of students with intellectual disabilities.MethodsThis research selected 26 mildly mentally disabled students in special education schools (age: 14.5 ± 0.8 years old), the subjects were randomly assigned to three groups by the digital randomization method, which badminton physical intelligence group (BSI), badminton group (BS) and control group (CON), with BSI conducting “physical intelligence” integration badminton intervention, and BS conducting badminton intervention, the intervention cycle was 12 weeks, with 3 teaching sessions per week, each session lasted for 40 min. The subjects’ cognitive abilities and basic motor skills were analyzed.ResultsThe results showed that BSI had highly significant differences in all cognitive ability test items (p < 0.01); BS had significant differences only in visual attention, visual memory, and motor imitation (p < 0.05). The results of incremental changes between groups before and after the intervention showed that BSI compared with CON had significant differences in all aspects except in object constancy (p < 0.05); BS compared with CON had higher incremental means than CON in visual attention, visual memory, and movement imitation, with significant differences (p < 0.05); BSI compared with BS had significant differences in all aspects except in object constancy and visual memory aspects, there is a significant difference (p < 0.05).ConclusionThe “Body-Smart Integration” badminton intervention can improve the cognitive ability of students with intellectual disabilities in visual, auditory, imitation, concept learning, object permanence, etc., and the effect of improving the cognitive ability of students with intellectual disabilities is better than that of the badminton group and the control group.